Sediment cooling triggers germination and sulfate reduction by heat‐resistant thermophilic spore‐forming bacteria. (2nd December 2019) - Bell, Emma; Sherry, Angela; Pilloni, Giovanni; Suárez‐Suárez, Ana; Cramm, Margaret A.; Cueto, Guillermo; Head, Ian M.; Hubert, Casey R. J.
Summary: Thermophilic endospores are widespread in cold marine sediments where the temperature is too low to support growth and activity of thermophiles in situ . These endospores are likely expelled from warm subsurface environments and subsequently dispersed by ocean currents. The endospore upper temperature limit for survival is 140°C, which can be tolerated in repeated short exposures, potentially enabling transit through hot crustal fluids. Longer‐term thermal tolerance of endospores, and how long they could persist in an environment hotter than their maximum growth temperature, is less understood. To test whether thermophilic endospores can survive prolonged exposure to high temperatures, sediments were incubated at 80–90°C for 6, 12 or 463 days. Sediments were then cooled by 10–40°C, mimicking the cooling in subsurface oil reservoirs subjected to seawater injection. Cooling the sediments induced sulfate reduction, coinciding with an enrichment of endospore‐forming Clostridia . Different Desulfofundulus, Desulfohalotomaculum, Desulfallas, Desulfotomaculum and Desulfofarcimen demonstrated different thermal tolerances, with some Desulfofundulus strains surviving for >1 year at 80°C. In an oil reservoir context, heat‐resistant endospore‐forming sulfate‐reducing bacteria have a survival advantage if they are introduced to, or are resident in, an oil reservoir normally too hot for germination and growth, explaining observations of reservoir souring following cold seawater injection.